Impact of the Conversion of Citrus Plantations to Oil Palm Plantations - Chinthea Sukphing; Sueoy Sehunae (Journal La Lifesci, 2021)
This article discussed about the conversion of agricultural land into other uses is one of the occurrences that has occurred fairly often in recent years. The method utilized with the purposive sampling , including but not limited to certain criteria that have been established. The informants that participated in this research were ten (10) individuals who were chosen based on a variety of factors. The kind of data that was utilized was qualitative data of a certain kind (descriptive). The result of this research is the factors that influence land use change: I external factors, which include economics and demographics, which cause the conversion of community citrus plantations to oil palm plantations under the pretext of abundant yields and income, in order to meet the daily needs of the community; (ii) internal factors, where farmers are greatly aided by the presence of this type of palm tree, due to its high productivity; and (iii) internal factors, which cause the conversion of community citrus plantations to oil palm plant Economically, the conversion of citrus farms to oil palm plantations has had a positive effect since the revenue from oil palm farming is higher than that from citrus farming.